Exploring the synergistic effect of NixSn2xS4x thiospinel with MWCNTs for enhanced performance in dye-sensitized solar cells, the hydrogen evolution reaction, and supercapacitors. Issue 16 (7th April 2020) - Saravanakumar, T.; Selvaraju, T.; Bhojanaa, K. B.; Ramesh, M.; Pandikumar, A.; Akilan, R.; Shankar, R.; Sardhar Basha, S. J.
Abstract : Trifunctional thiospinel-like M–Ni x Sn2 x S4 x nanocomposite was synthesized with ease. Abstract : Trifunctional nickel tin sulfide (Ni x Sn2 x S4 x ) with a thiospinel-like structure composited with multiwalled carbon nanotubes (MWCNTs) (M–Ni x Sn2 x S4 x ) was synthesized by a facile method. The unit cell arrangement of the prepared composite was studied by density functional theory, and the theoretical interpretation satisfactorily inferred the presence of a synergistic effect between the thiospinel and MWCNTs. The high metallic conductivity and superior electrocatalytic activity of the M–Ni x Sn2 x S4 x composite endow it with diverse applications. The composite shows promise as a counter electrode for dye-sensitized solar cells (efficiency of 4.67% for fluorine-doped indium tin oxide compared to 5.23% for platinum); an efficient catalyst for the hydrogen evolution reaction with good cycling stability and a low overpotential of −41 mV at a cathode current density of 10 mA cm 2 and a Tafel slope of 43 mV dec −1 on a graphite sheet electrode; and an impressive capacitance material on a graphite sheet electrode alternative to expensive current collectors such as Ni foam, with a specific capacitance value of 1200 F g −1 at a current density of 1 A g −1 and a long life span of 92.6% that is retained for up to 15 000 cycles.